Ecotecture econocrete promoting sustainable landscape construction using coconut (Cocos nucifera L.) shell as alternative fine aggregate of lightweight concrete - Ricohermoso, Andrei Yvone R.; Bello, Jaclyn alexandra Marie B.; Dul-loog, Vic L. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
Coconut is a top agricultural crop in the Philippines with up to 5.76 million tons of residue per year. As a renewable resource, coconut waste provides great potential to produce biobased materials. In sustainable concrete studies, coconut shells were presumed to be a compatible lightweight aggregate with cement as an alternative to coarse aggregate. Coconut shell concrete exhibited better resistance to crushing, impact, and abrasion, decreasing the material's overall density while increasing its performance. With an increasing demand for construction and natural aggregate production, these show promising results in using coconut waste as an alternative construction material for concrete, particularly for landscape construction. CSFA, as a lightweight aggregate, produced lightweight concrete for nonstructural applications, with an optimal and acceptable percentage replacement of 25 and 50, respectively. CSLC with 25 percent FA replacement had greater compressive strength and lower density than conventional lightweight concrete, but an increase in CSFA replacement reduced its compressive strength and density. CSC pavers, with the optimum FA replacement, were observed with a water-resistant, smooth, light-colored surface and was publicly perceived to be sufficiently durable, slip resistant when dry, and safe and comfortable for walking. However, it can be improved and modified to be more suitable for outdoor use, specifically for pedestrian pavements. Through a comparative analysis of resource flow of CSLC and conventional concrete, it was found that the resource optimization and circulation of coconut shells as an alternative FA could provide resource efficiency and conservation of natural aggregates. CSLC could contribute to environmental sustainability and green building, fostering a circular economy through CSFA in concrete production.
Include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Coconut shell concrete; Sustainable landscape architecture; Sustainable construction; Circular economy